PENGARUH KEPUASAN KERJA, QUALITY OF WORK LIFE, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN PADA ROSALI HOTEL & RESTAURANT DI SITUBONDO - Mega Anjar Widyabakti; Bayu Wijayantini; Rusdiyanto Rusdiyanto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
Performance describes the results of complete and high-quality work achieved by employees when doing tasks in accordance with the dependents given to the employee. The type of research used is quantitative research and data collection techniques using questionnaires, interviews and documentation of 32 respondents. The analytical tool used in this research is multiple linear regression analysis. The test results show that job satisfaction, quality of work life, organizational commitment have a significant effect on the employee performance of Rosali Hotel & Restaurant. Then from the three independent variables, it is known that the job satisfaction variable (X1) has the most dominant effect on employee performance variables at Rosali Hotel & Restaurant compared to other independent variables used in this study. This study is only able to explain the performance of employees by 44.2%, so there are other factors outside the model under study that are able to explain employee performance.